반응표면분석법을 이용한 설탕, 펙틴, 구연산 첨가 생강배잼의 품질 특성 및 제조조건 최적화 연구 - 이지은(Ji Eun Lee); 박세영(Se Young Park); 유현희(Hyeon Hee Yu); 노정옥(Jeong Ok Rho) (동아시아식생활학회지, 2021)
This study examined the optimal mixing quantities of sugar, pectin, and citric acid for the preparation of ginger pear jam. The experiment was designed according to the central composite design of response surface methodology (RSM). To develop the jam using RSM, sugar, pectin, and citric acid were set as the independent variables. The experimental data on physicochemical properties, and sensory evaluation were fitted to various models. Among the responses, pH (p<0.001), sugar content (p<0.001), spreadness (p<0.01), L-value (p<0.001), a-value (p<0.001), and b-value (p<0.001), and the sensory properties of appearance (p<0.01), taste (p<0.05), and overall acceptability (p<0.05) showed significant correlations with sugar, pectin, and citric acid. From these results, the optimal formulation was calculated by applying numerical and graphical methods, and was determined to be 250 g pear paste, 175 g sugar, 4 g pectin, and 0.8 g citric acid. We believe that manufacturing ginger pear jam using sugar, pectin, and citric acid promotes the consumption of local agricultural products, and contributes toward the development of functional jams tailored to preferences of the consumer. KCI Citation Count: 0